Social Identity and Altruism during Crisis Situations: Social Groups Solidarity - Albab, Ulul; Hakim, Abdul; Muzakki, Muhammad; Rahmawati, Intan (Research Synergy Foundation, 2025)
This study investigates how social identity influences altruistic behaviors during the COVID-19 pandemic in Indonesia, drawing on Social Identity Theory by Burke and Stets (2000). It examines how individuals and groups activate social identities that motivate pro-social behaviors during a global health crisis. Three key figures from civil society organizations illustrate how identities rooted in shared values of humanitarianism drive actions prioritizing collective welfare, through advocating for equitable healthcare and vaccine access. Through interviews and qualitative analysis, this research reveals that social identity fosters altruism beyond national boundaries, promoting shared well-being for Indonesian people. These findings contribute to literature on social identity by highlighting how global crises can enhance collective empathy and encourage actions that social entrepreneurs could leverage periods of widespread crisis to mobilize support and engagement for their initiatives. While the study draws from a small, purposive sample of civil society leaders during the early COVID-19 period, which limits generalizability, its value lies in uncovering the social identity–based motivations that drive cooperation in times of crisis. By highlighting why individuals engage in collective action—not only because it is morally commendable but also because it reflects identity commitments—the research offers insights for strengthening civic engagement, inclusive crisis responses, and supporting grassroots as well as high-profile forms of altruism in future humanitarian contexts.